Mechanical response of unidirectional composite bars loaded in transverse compression. (15th July 2016) - Tanks, Jonathon D.; Harris, Devin K.; Sharp, Stephen R.
Abstract: Unidirectional carbon fiber reinforced polymer (CFRP) bars and cables are used in numerous high-performance applications as tensile load-bearing elements. In most cases, this requires a mechanical gripping device to apply tension to the rod, which is a transversely isotropic material. This paper investigates the response of CFRP bars under transverse compression, a loading scenario inspired by mechanical anchorage systems and couplers. The deformation and failure of four commercially available bars were compared with respect to their matrix type (two epoxy, two vinylester) and surface finish (three coated with sand, one wrapped in fibrous textile). The fiber-wrapped bar was further examined to understand the deformation process during loading: full-field strain was measured using digital image correlation (DIC) and compared to analytical and numerical models. Bars with sand-coating show significantly reduced capacity when loaded in transverse compression compared to the fiber-wrapped surface, and microscopy reveals areas of localized contact with sand particles that support test results. For fiber-wrapped bars, both models show close agreement with DIC in terms of shear strain magnitude and characteristic response. Implications for developing tensioning anchorage systems with CFRP bars are discussed.